2023
DOI: 10.1038/s41588-023-01420-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of thoracic aortic aneurysm and dissection in the Million Veteran Program

Abstract: The current understanding of the genetic determinants of thoracic aortic aneurysms and dissections (TAAD) has largely been informed through studies of rare, Mendelian forms of disease. Here, we conducted a genome-wide association study (GWAS) of TAAD, testing ~25 million DNA sequence variants in 8,626 participants with and 453,043 participants without TAAD in the Million Veteran Program, with replication in an independent sample of 4,459 individuals with and 512,463 without TAAD from six cohorts. We identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Interestingly, the ascending aorta seems more influenced by diabetes and glycemic traits than the descending aorta. Previous research indicated that the vascular smooth muscle cells of the thoracic ascending aorta have a distinct embryonic origin from the rest of the arterial tree, arising from neural crest cells [ 40 ]. Given that, we theorize that the ascending thoracic aorta may be more susceptible to diabetes and disruptions in glycemic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ascending aorta seems more influenced by diabetes and glycemic traits than the descending aorta. Previous research indicated that the vascular smooth muscle cells of the thoracic ascending aorta have a distinct embryonic origin from the rest of the arterial tree, arising from neural crest cells [ 40 ]. Given that, we theorize that the ascending thoracic aorta may be more susceptible to diabetes and disruptions in glycemic balance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it cannot be excluded that the early-onset cases, including those described by Van Gucht et al [24] and Guo et al [23], are caused by additional genetic defects that have not been found. Indeed, there are reports suggesting the role of digenic/oligogenic/polygenic inheritance in TAA [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up in vitro studies suggested that upregulation of TCF7L2 , which encodes a transcription factor in the Wnt (wingless-related integration site)/β-catenin pathway, leads to BCL2 repression and thus increased VSMC apoptosis. Most recently, Klarin et al 14 published a GWAS of 8626 individuals with TAAD in the Million Veteran Program, with replication in 6 external cohorts, and identified 21 TAAD risk loci. Genome-wide copy number variation analyses have identified an enrichment of copy number variation regions in sporadic TAAD cases, although none of these individual associations achieved statistical significance.…”
Section: Gwas For Aortic Traitsmentioning
confidence: 99%